Deformation modes investigation during ex-situ dwell fatigue testing in a bimodal near-α titanium alloy. (October 2022) - Fernández Silva, B.; Kawalko, J.; Muszka, K.; Jackson, M.; Fox, K.; Wynne, B.P.
Highlights: Basal slip and 10 1 ¯ 2 < 11 2 ¯ 0 > tensile twins were found active on hard orientated grains and colonies respectively. Observations of Rogue pairs were experimentally observed matching hypothesis crystal plasticity models for quasi-cleavage facet formation. A common slip was observed at Rogue colony-grain combinations in a bimodal microstructure. Abstract: In this paper, quasi-cleavage facet formation and deformation mechanisms in dwell fatigue have been studied on specimens from a Ti834 compressor disc alloy with a bimodal microstructure by ex-situ dwell fatigue testing at temperatures between 80 °C and 200 °C. Basal slip was observed in grains with their c-axis near parallel the loading direction, while colonies similarly oriented accommodate deformation by tensile twins 10 1 ¯ 2 < 11 2 ¯ 0 > . This type of slip in basal planes is the most critical damage mode leading to failure during dwell fatigue loading. A Rogue colony-grain combination is presented and a possible criterion for slip transfer in bimodal titanium alloys is introduced. The requirements cited for quasi-cleavage facet formation leading to dwell fatigue failure have been experimentally observed in agreement with the suggested hypothesis in previously presented crystal plasticity models.